Environmental biocontamination by SARS-CoV-2 Virus in the hospital setting - M Espejo Mambié; D San Jose-Saras; C Bischofberger Valdés; C Díaz-Agero Pérez; JC Galán Montemayor; L Martínez-García; M Abreu Di-Berardino; P Moreno-Nunez; J Vicente-Guijarro; J.M Aranaz-Andrés (Current Research in Microbial Sciences)
Background: Demonstrating the capability to isolate biological material from the environment was fundamental to supporting any transmission route. Various and inconsistent methodologies have been used to address this issue; however, the debate in scientific societies about the possibility of airborne transmission as a source of SARS-CoV-2 spread remained open. Objective: To analyze SARS-CoV-2 contamination in the air and on surfaces in a hospital setting during the COVID-19 pandemic. Methods: This study involved air and surface sampling in the emergency, hospitalization, and intensive care unit areas of the Ramón y Cajal University Hospital. A consistent methodology was used for all samples, and clinical and environmental parameters and characterization of each location were recorded. Results: A total of 234 samples were collected, comprising 160 surface samples and 74 air samples, of which 6.84 % tested positive (13/160 surface samples and 3/74 air samples). High-contact surfaces had the highest proportion of positive samples (12/13). All positive air samples were identified within 2 m of patients who had recently developed symptoms (<5 days). High dependency and elevated temperatures seemed to indicate a higher risk of environmental biocontamination. Additionally, there was a higher risk of contamination in the intensive care units than in the hospitalization or emergency units.